Design and Implementation of Web-Based Archive Management Information System - Mewengkang, Alfrina; Sengkey, Marssel Michael; Lengkong, Jeffry Sony Junus; Rotty, Viktory Nicodemus Joufree (JR Education, 2022)
The purpose of this research is to create an archive management information system. Most of the study programs within the University have not used a web-based archive management information system, even though this is a supporting factor in college and university accreditation. The research method used is the prototype development method. In this method there are 4 (four) stages, namely: (1) Communication, (2) Quick Plan and Modeling Quick Design, (3) Construction Of Prototype, (4) Deployment Delivery & Feedback. At the Deployment Delivery & Feedback stage, the researcher uses a testing method with a black-box testing approach. In this black box testing phase, there are three testing processes, namely (1) Incorrect functions, both input and output, (2) Interface errors, (3) Errors in data structure or database access. From the research conducted to obtain good results and from these results the researchers concluded that the web-based archive management information system is in accordance with the research objectives and is suitable for use in the data archiving process